2015
DOI: 10.1371/journal.pone.0121934
|View full text |Cite
|
Sign up to set email alerts
|

The Benefits of Social Influence in Optimized Cultural Markets

Abstract: Social influence has been shown to create significant unpredictability in cultural markets, providing one potential explanation why experts routinely fail at predicting commercial success of cultural products. As a result, social influence is often presented in a negative light. Here, we show the benefits of social influence for cultural markets. We present a policy that uses product quality, appeal, position bias and social influence to maximize expected profits in the market. Our computational experiments sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(47 citation statements)
references
References 21 publications
1
46
0
Order By: Relevance
“…In this model, users chose from a list of items ranked by quality rather than popularity; this modification makes the market predictable and aligns popularity and quality. Empirical tests of specific presentation policies combining quality and popularity do suggest that uncertainty can be reduced in this way 28 , 29 . Finally, Becker et al .…”
Section: Introductionmentioning
confidence: 99%
“…In this model, users chose from a list of items ranked by quality rather than popularity; this modification makes the market predictable and aligns popularity and quality. Empirical tests of specific presentation policies combining quality and popularity do suggest that uncertainty can be reduced in this way 28 , 29 . Finally, Becker et al .…”
Section: Introductionmentioning
confidence: 99%
“…it maximises the expected number of downloads. This result was proved by [1] for the performance ranking and by [32] for any static ranking such as the quality ranking. Unfortunately, sublinear social signals are not always beneficial to the market in that sense, as one can see in Example 7.1.…”
Section: Additional Observations On Sublinear Social Signalsmentioning
confidence: 79%
“…Abeliuk et al [1] have shown that these values can be recovered accurately and quickly, either before or during the market execution using the approximation suggested by Krumme et al: The objective of the firm running this market is to maximise the total expected number of purchases. To achieve this, the key managerial decision of the firm is what is known as the ranking policy [1], which consists in deciding how to display the products in the market (e.g., where to display a product on a web page). Here we assume that, at the beginning of the market, the firm decides upon a ranking for the items, i.e., an assignment of items to positions in the marketplace.…”
Section: The Trial-offer Modelmentioning
confidence: 99%
See 2 more Smart Citations